Posterior reversible encephalopathy syndrome (literature review) - E. A. Kovaleva; L. Kh.-B. Akhmatkhanova; T. A. Magomedov; E. V. Shevchenko; M. M. Khakhova; G. R. Ramazanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Posterior Reversible Encephalopathy Syndrome (PRES) – a clinical and radiological syndrome characterized by acute cerebral endotheliopathy, impaired permeability of the blood-brain barrier with limitations of vasogenic cerebral edema, usually of the occipital and posterior lobes, and known to develop mental illnesses such as headache, decreased alertness, seizures, and visual disturbances. The initial manifestations of the disease are associated only with arterial hypertension, but after investigating the phenomenon, PRES can also be caused by other factors such as infections, kidney disease, or the use of certain medications. This article will discuss the main causes of PRES, the consequences and methods of verifying the manifestation, as well as the principles of treatment of this condition.